Avaliação biomecânica dos membros inferiores e do tronco de atletas de voleibol durante aterrissagem pré e pós aplicação de protocolo de exaustão - Carvalho, Caio Augusto Mendes de (2020)
Introduction: Volleyball athletes are common to exhaustion during training and competitions, due to the amount of demand, including jumps, to which they occur, which could increase the risk of injury. Objective: to evaluate the movements of the lower limbs and trunk through kinematics, surface electromyography and force platform, during the landing of a maximum vertical jump, before and after the application of an exhaustion protocol. Methods: 26 competitive female volleyball athletes were evaluated. An exhaustion protocol was applied pre and post, a kinematics of the lower limb and trunk, in the sagittal and frontal planes, an electromyographic analysis of the Rectus Femoris (RF) and Middle Gluteus (Gmed) muscles, and the landing power. Results: In the comparison before and after exhaustion, an increase in knee flexion and valgus after exhaustion was observed. Regarding the electromyographic evaluation, there was no difference in muscle activity, just as there was no difference in the average power of the heel height before and after exhaustion. Conclusion: based on the results, changes related to the movement pattern in the knee joint, as a probable strategy to reduce the overload on landing after exhaustion. On the other hand, no changes were found in the electromyographic activity of the RF and Gmed muscles, nor for the variable power of the jump before and after exhaustion.